ACROCHORDON: AN UNCOMMON TUMOUR LIKE GROWTH IN DOGS - Ravi Mohan Shukla; J. Selvaraj; N. Babu Prasath; K. Jayakumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Three cases of acrochordon were diagnosed by gross, cytological and histopathological examinations. Each case was an unique presentation, in which patient exhibited a soft, pendulous mass on the ventral thorax, right thigh and a small, firm growth on the tail. The affected animals were a six-year-old Rottweiler bitch, a four-year-old Labrador bitch and a six-year-old Labrador dog. All the animals appeared clinically normal. On gross examination, the growths were pendulous, soft and ulcerated. The cut surface appeared creamy white in colour. Cytological analysis of impression smears revealed individual to multiple spindle cells. Histopathological examination revealed a redundant dermal fibrous tissue covered by a hyperplastic epidermis. The stromal component appeared more prominent in these cases. Based on the gross and histopathological features, the cases were diagnosed as acrochordon.